Помогите прошу!
1) (а-4)(а+4) - 2а(3 - а)=
2) (4х - 3)^2- 6x (4 -x)=
3) (a-8)(a-7) - (a-9)^2=
4) (p+3)(a- 11)+(p+6)^2=
5) (b+3)(b - 3)+(2b+3)^2 =
6) (a - x)^3 +(a+x)^2 =
7) 3(x-5)^2 +(10x - 8x^2)=
8) 2(x+6)^2 - (20x+70) =

1

Ответы и объяснения

2014-03-30T13:59:16+04:00
1)(а-4)(а+4) - 2а(3 - а)=а в квадрате+4а-4а-16-6ф+2а в квадрате=а в квадрате-16-6а+2а в квадрате=3а в квадрате-6а-16
2)
(4х - 3)^2- 6x (4 -x)=8х-6-24х+6х в квадрате=6х в квадрате-16х-6
3)(а-8)(а-7)-(а-9)*2=а в квадрате-7а-8а+56-2а+18=а в квадрате-15+56-2а+18=а в квадрате-17а+74
4)(р+3)(а-11)+(р+6)*2=ар-11р+3а-33+2р+12=ар-9р+3а-21
5)
 (b+3)(b - 3)+(2b+3)^2 =в в квадрате-3в+3в-9+4в+6=в к вадрате-9+4в+6=в в квадрате+4в-3
6)(a - x)^3 +(a+x)^2 =3а-3х+2а+2х=5а-х
7)3(x-5)^2 +(10x - 8x^2)=3х-30+10х-16х=-3х-30(можно поделить на (-3) и тогда будет:х+10)
8)2(x+6)^2 - (20x+70) =2х+24-20х-70=-18х-46